The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/adfm.202212730
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Lesion Cells and Targeted Mitochondria Via Embedded Hydrogel Microsphere using Heat Transfer Microneedles

Abstract: The localization of lesion cells and targeted regulation of organelle function can promote the lesion repair. However, conventional regulation is difficult to reach deep lesions and target mitochondria. In this study, dynamic spiral Mosaic technology is ued to construct heat transfer microneedles with spiral Mosaic micro/nano hydrogel microspheres (ST-needle), using molecular chain motion in response to heat stimulation to regulate the adhesion of nonoriented triblock polymer, as a dual delivery system for hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…An ST-needle embedded with functionalized hydrogel microspheres was constructed to develop the ST-needle composite system. Using the molecular chain motion triggered by thermal response to adjust the adhesion property of a nonoriented triblock polymer, the system enables the dual-localized delivery of physical and biological factors ( 34 ). Drawing inspiration from conductive CA-needles, the combination of functionalized hydrogel microspheres and localized conductive microneedles facilitates the dual positioning regulation of electrical energy and the delivery of biological factors, which represents a previously unknown biomaterial system with notable developmental potential.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An ST-needle embedded with functionalized hydrogel microspheres was constructed to develop the ST-needle composite system. Using the molecular chain motion triggered by thermal response to adjust the adhesion property of a nonoriented triblock polymer, the system enables the dual-localized delivery of physical and biological factors ( 34 ). Drawing inspiration from conductive CA-needles, the combination of functionalized hydrogel microspheres and localized conductive microneedles facilitates the dual positioning regulation of electrical energy and the delivery of biological factors, which represents a previously unknown biomaterial system with notable developmental potential.…”
Section: Resultsmentioning
confidence: 99%
“…5B). We previously demonstrated that this system is capable of delivering functionalized hydrogel microspheres to lesion sites using a thermoelectric acupuncture instrument to activate the dynamic Van der Waals force mechanism ( 34 ). The use of the conductive ST-needle system enables minimally invasive insertion of the needle tip into the deep layer of cartilage, precise localization of the cartilage lesion, and release of electrical energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugating TPP with poly (D, L‐lactic acid ‐co‐ glycolic acid)‐poly (ethylene glycol)‐poly (D, L‐lactic acid ‐co‐ glycolic acid; PLGA–PEG–PLGA), a thermosensitive polymer, can release therapeutic agents (i.e., mitophagy inducer: Parkin protein) into the mitochondria at the deep cartilage and even the subchondral bone, controllably and accurately at the guidance heat energy. [ 59 ] The potential future prospects for OA could be an integration strategy equipped with hierarchical targetability and responsibility for the synergistic microenvironment regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al designed heat transfer microneedles with spiral Mosaic micro/nanohydrogel microspheres (ST needles). 106 Hydrogel microspheres containing the biological factor PARKIN protein are loaded into the threaded groove of the ST needle using a thermosensitive adhesive triblock copolymer so that they can pass through the barrier of cartilage on the ST needle with the double protection provided by the threaded groove and the viscous polymer. In response to thermal stimulation with molecular chain motion, the hydrogel microspheres will detach from the needle body.…”
Section: Application Of Mns In the Musculoskeletal Systemmentioning
confidence: 99%